EFEKTIVITAS PENGELOLAAN OBJEK PARIWISATA WILAYAH WOLOAN RAYA KECAMATAN TOMOHON BARAT KOTA TOMOHON - MAKAL, JOHANNA; LENGKONG, FLORENCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
Tourism is a service industry which is a barometer of economic growth, especially in creating sustainable development. Seeing developments in the tourism sector which is increasingly rapid, it turns out that there are still problems that make the management of tourism objects in Woloan ineffective. So that this study aims to determine the effectiveness of the management of tourism objects in the Woloan Raya area, West Tomohon District, Tomohon City. The research method used is descriptive qualitative. The focus of this research is based on the opinion of Duncan and Steers with four indicators to measure effectiveness, namely: integration, adaptation, quality, and external assessment. Sources of data collected in this study is through primary data and secondary data. The data collection techniques in this research are observation, interviews, and documentation. With nine informants consisting of managers of tourist objects and tourists. Based on the results of the study, it shows that the management of tourism objects in the Woloan Raya area is still not effective, where the quality of services provided is still lacking due to a lack of discipline and knowledge about good tourism governance, inadequate facilities, no realization of programs for the development of related tourism objects, and lack of interaction between tourism object managers and tourists. So it is necessary to improve the quality of service, improve the quality and quality of the infrastructure provided, and build communication with tourists to get an assessment or response related to the management of tourism objects. Keywords: Effectiveness, Management, Tourism